Jewish Day-School Growth in Toronto: Freeing Policy and Research from the Constraints of Conventional Sociological Wisdom - Pomson, Alex (Canadian Journal of Education/Revue canadienne de l’éducation, 2002)
The recent growth of Jewish day schools in the United States and United Kingdom has consistently been attributed to the declining appeal of public education among minority groups in general and the Jewish community in particular. In this article I review the interpretative heuristic that lies behind this claim, and ask whether this heuristic accounts for day-school growth in Toronto. I examine previously unpublished school enrolment data and conclude that Jewish families are neither in flight from the Toronto public school system nor are they heading in increasing numbers to day schools. I suggest, therefore, that the prevailing cross-cultural paradigm for day-school growth needs reassessing in a Canadian context and perhaps beyond. Keywords: Jewish day school, school choice, cross-cultural analysis L’essor récent des externats juifs aux États-Unis et dans le Royaume-Uni a été souvent attribué au déclin de l’attrait qu’exerce l’enseignement public sur les minorités en général et la communauté juive en particulier. Dans cet article, l’auteur examine l’heuristique interprétative qui est sous-jacente à cette affirmation et se demande si cette heuristique explique l’essor des externats à Toronto. Il analyse des données non publiées jusqu’ici sur les inscriptions et conclut que les familles juives ne sont ni en train de fuir le système d’enseignement public ni en train de se diriger en nombre croissant vers les externats. Il formule plutôt l’hypothèse que le paradigme transculturel dominant relatif à l’essor des externats a besoin d’être réévalué dans un contexte canadien et peut-être même plus vaste. Mots clés : externat juif, choix d’école, analyse transculturelle